EKONOMI KELEMBAGAAN BARU DAN KEBIJAKAN SEKTOR PUBLIK BEBERAPA CONTOH KASUS - Sof yan (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2019)
This paper talks about the economic theory of institutions and public policy which has recently become a broad topic discussed and applied to various fields of public policy. In the course of economic history, market failures have occurred. That is the occurrence of a distortion in the direction of balance which has an impact on the market's inability to fulfill all community needs, in addition to the emergence of property rights. Institutional Economics consists of 2 (two) parts namely the Old Institutional Economy and the New Institutional Economy. This paper discusses new institutional economics with various case examples. such as the concept of Bounded Rationality, Asymmetric Information, Principal Agent Theory, Institutional Change, Social Change, Right Property, Hierarchy, Integration, Corporate Governance and Profit Sharing